Creative Arts and the Indigenous Healing Circle Within an Indigenous Context - France, Honoré (Canadian Journal of Counselling and Psychotherapy, 2020)
Within Indigenous cultures, there is a long tradition of the creative arts being interconnected within the everyday lives of human beings. Art, culture, and spirituality are the connections that are reflected in daily living. From a healing perspective, these connections remain one of the most successful ways of working with people. Through the lens of culture, specific clinical examples will show how the creative arts in therapy can be used with music, drumming, drama, storytelling, and woodcarving. Specific clinical examples involving these creative arts forms and residential school survivors are described to demonstrate the healing power of the creative arts in therapy from an Indigenous perspective.